LEGAL CERTAINTY OF ALTERNATIVE DISPUTE RESOLUTION MEDIATION - Sasmiar; Umar Hasan; Suhermi (Universitas Bengkulu, 2024)
If you look deeper into the substance of arbitration, the regulations are more dominant compared to the regulations regarding alternative dispute resolution. This arrangement is very important regarding the legal capacity of a mediator in carrying out his mediation function. Alternative dispute resolution in Indonesia is a tradition that has been implemented for a long time, such as in customary law in rural communities. An alternative model for resolving disputes in customary law communities is carried out by means of deliberation to reach a consensus. Dispute resolution through mediation is much more effective and efficient in terms of time, energy and costs when compared to dispute resolution through court. the process of resolving disputes through mediation is final and binding. The method used in this research is normative juridical. where doctrinal research is related to mediation within the framework of norms that have been abandoned or there is a legal vacuum. the rules regarding mediation are very simple while the legal requirements are increasing. the substance of the mediation arrangements is incomplete, such as arbitration. National legal product was regulated arbitration and alternative dispute resolution. in addition to being able to resolve civil disputes to general courts, there is also the possibility of submitting them through arbitration and alternative dispute resolution. laws arbitration and alternative dispute resolution such as mediation do not have legal certainty, because the substance of the mediation arrangements is incomplete. This is certainly detrimental to the disputing parties. Supreme Court regulated vacuum law to control this legal proceeding. The mediation process is carried out based on the practices that apply in the field. This is certainly detrimental to the disputing parties, and reduces public interest in resolving their disputes through mediation Keywords: Dispute Resolution; Mediation; Legal Certainty